Preparation of Al-Ga-In-Sn-Bi quinary alloy and its hydrogen production via water splitting. (9th February 2015) - Huang, Tianping; Gao, Qian; Liu, Dan; Xu, Shaonan; Guo, Chunbin; Zou, Jingjing; Wei, Cundi
Abstract: An Al-Ga-InSn4 -InBi quinary alloy was prepared by a simple smelting and casting method. The phase components and microstructures of the quinary alloy were investigated by means of XRD and SEM with EDX. Two different intermetallic compounds of InBi and InSn4 were simultaneously found in the alloy. Al-Ga-In3 Sn and Al-Ga-InSn4 quaternary alloys were prepared in the same way for comparison purpose. The reactions of alloys with water were performed at different water temperatures ranging from 30 to 60 °C. Compared with quaternary alloys, Al-Ga-InSn4 -InBi not only can react with water continuously and completely, but also exhibit a relatively more stable hydrogen production rate. Owning to the controllable and everlasting features, the Al-Ga-InSn4 -InBi quinary alloy could be more suitable in the field of proton exchange membrane fuel cell (PEMFC) as a fuel provider. Moreover, the reaction of Al with other low melting point metals were measured by DSC. Based on DSC analysis and other results, an activation mechanism was supposed. Graphical abstract: In this paper, a quinary alloy Al-Ga-InSn4-InBi was newly prepared and its phase compositions and microstructures were investigated by means of XRD and SEM with EDX. As seen in the figure, the alloy mainly consists of three phases: Al(Ga) solid solution (columnar grains), intermetallic compound InBi and InSn4 (irregular shape and granular shape small particles exist along grain boundaries). The general hydrogen generation performance of this alloy is superior to quarternary alloys Al-Ga-InSn4 and Al-Ga-In3 Sn. The effect of water temperature on hydrogen generation performance of alloys was studied. Highlights: We newly prepared Al-Ga-InSn4 -InBi quinary alloy. This alloy can be used to generate hydrogen online. This alloy produces hydrogen more mildly and persistently than quarternary alloys. Effect of phase components on hydrogen generation of this alloy is investigated.